ATTACHMENT STYLE AND ITS INFLUENCE ON EMOTIONAL INTELLIGENCE AMONG YOUNG ADULTS - Maheshwari, Aruna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The well-being of an individual depends on many factors, emotional intelligence is one of these factors and affected by different attachment styles. Emotional Intelligence is the capability to recognize and understand own emotions as well as the emotions of others whom an individual interacted. Attachment style define the identification of consistent and observable emotional and behavioural responses in close relationships. The purpose of present study to find out the effect of different attachment styles on emotional intelligence among young adults. Emotional Intelligence and Attachment style of 96 young adults of age group of 18-30 years (45 males and 51 females) were assessed by Adult Attachment Scale (ASS) and The Schutte Self-Report Emotional Intelligence Test (SSEIT). Digital survey method was adopted to reach out to the young adult population and Pearson correlation coefficient method used to establish functional corelation between independent variables and dependent variable. The degree of influence of the variables on emotional intelligence was determined using linear regression, and a regression equation was derived. The results of the questionnaire-based survey suggest that different attachment styles are significantly correlated with emotional intelligence. Regression analysis also shows that secure attachment style successfully predicts emotional intelligence. These findings indicate that an individual with secure attachment is able to aware and deal with his/her emotions yet maintain control over difficult situations.